The Development of the Integrated STEAM Approach Using Social Service Learning to Address Students' Creativity - Prasertsang, Parichart; Charoensuk, Kamonphop; Polyiem, Titiworada (International Journal of STEM Education for Sustainability, 2024)
This research aimed to develop an integrated STEAM approach using social service learning to address students' creativity. The research is conducted using RD methodology with 3 phases; Phase 1: Analysis of documents and concepts Theory Research related to the integrated STEAM approach using social service learning Phase 2 Create a integrated STEAM approach using social service learning, and Phase 3: Study the results of using an integrated STEAM approach using social service learning. The sample is a network of STEM schools in Roi Et province, Thailand. One school was drawn using the school as a random unit, and there were 30 students in the product design course offered in the second semester of the academic year 2023.  The tools used to collect data include a integrated STEAM approach using social service learning, a measure of creativity from the artworks of students learning with art activities using the behavioral observation and corporate social responsibility assessment. The statistics used in the analysis were percentage, mean, and standard deviation. The results showed that the teaching and learning model by social service has 6 components; namely basic principles, concepts, and theories related to teaching and learning by social service, objectives of the teaching and learning model, teaching procedures social system response principle, and the support system is called "PIPAR MODEL". P-Preparation, -Imagine, P-Presentation, A-Action, And the R-Reflect stage can encourage the creativity of 4th-grade students. To have a creative score of 80 percent, 100 percent, and “PIPAR  MODEL” can also develop students to be socially responsible, and socially responsible to a large extent. It has a mean of 4.30 and a standard deviation of 0.612. It has a maximum mean of 4.70 and a standard deviation of 0.460. Second, students have respect for the rights of others. It has a mean of 4.64 and a standard deviation of 0.538. It has a mean of 3.78 and a standard deviation of 0.707.